Statistical Issues of Debt Conversions. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper examines two aspects of debt conversions. First, it examines general aspects of secondary markets of developing countries' bank debt, and the debt conversions that have taken place in a number of developing countries experiencing debt servicing difficulties. Second, by using common characteristics of debt conversion transactions, the paper analyzes the effects of debt conversions on monetary, balance of payments, and fiscal accounts in the debtor countries. It concludes with discussions on implications of debt conversions for reports of external debt statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet